Biochemical Oxygen Demand Concentration of Two River Basins in Selangor - Lai, Food See (1983)
This paper presents some interpretive notes on biochemical oxygen demand (B.O.D.) of Sungai Kelang and Sungai Selangor river basins located in the State of Selangor, Peninsular Malaysia. Simple statistical analysis was carried out to interpret the water quality using B. D.D. as an indicator of pollution level. Results showed steady deterioration of water quality with the level of urban development. There is also an important indication that short term variations of B.O.D. levels is high in all sampling stations.